Classroom CG by Guidance and Counseling Teachers to Improve Student Self-Control - Askiyaur Ramadhan; Mafruhah; Choli Astutik (Institut Agama Islam At-Tahdzib, 2026)
This study aims to describe Classical Guidance (CG) by a Guidance and Counseling Teacher (GCT) to improve students’ self-control. The study was conducted at Madrasah Aliyah (MA) Al-Amien Jambu Lenteng Sumenep under conditions of limited infrastructure. The study used a descriptive-qualitative method with one GCT and 16 students selected through purposive sampling techniques as research subjects. Data were collected through non-participant observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman Model. The results showed that GCT implemented CG through the planning stage (needs identification); organizing (schedule coordination); implementation (introduction, core, closing), and: follow-up (monitoring). GCT optimized the use of interactive lecture methods, group discussions, and creative use of whiteboards with colored markers and visual schemes. CG effectively improved students’ self-control. Students showed positive changes in their ability to control behavior in class, control emotions, manage learning time, and sharpness in decision-making. The main challenges include limited media, limited time duration, and the influence of the environment outside the school. The creativity and competence of GCT are the keys to the success of CG in conditions of limited facilities.